Inclusão de sal na ração e a toxicidade do nitrito em alevinos de jundiá (Rhamdia quelen) - Lima, Ronaldo Lima de (2005)
Nitrite is a nitrogenous residue that has several toxic effects on fish, being one of the most important the hemoglobin oxidation, causing hypoxia and death. Therefore, the objective of this work was to verify the survival and growth of silver catfish fingerlings (Rhamdia quelen) exposed to nitrite in the water and fed diets containing different levels of sodium chloride. In the experiment I the 96 h lethal concentrations (LC50-96h) of nitrite were determined using 5 nitrite concentrations in the water for each level of inclusion of NaCl in the food (0, 1, 2, 4, and 6%). In the experiment II the effect of 4 nitrite concentrations was verified (0.06, 0.46, 1.19, and 1.52 mg/L nitrite) for the feed without NaCl addition. The values of LC50-96h for nitrite were 20.46 ± 2.76, 21.37 ± 0.84, 11.86 ± 3.91, 21.37 ± 0.71, and 24.63 ± 4.88 mg/L nitrite, respectively, for the levels of inclusion of NaCl in the food of 0, 1, 2, 4, and 6%. There was no significant difference in relation to survival with the increase of the sodium chloride levels in the food. In the growth experiment 100% mortality rate was observed in the treatment with 1.52 mg/L nitrite after 20 days. Nitrite levels did not change weight, specific growth rate, and food conversion significantly among the treatments after 20 and 40 days. After 40 days the lowest biomass was verified in the treatment with 1.52 nitrite mg/L. The increase of nitrite concentration significantly reduced the standard length and increased the coefficient of variation of weight. The coefficient of variation of length increased significantly with the increase of time of exposure to nitrite. According to the results, the safe level of nitrite for growth of silver catfish fingerlings is below 1.19 mg/L (5,8 % of LC50-96h of the treatment without addition of salt in the food).